Inventory Information System: Optimizing Inventory Management for Company Business Sustainability - Hannatama Manik (SAN Scientific, 2023)
This research aims to investigate and describe the impact of implementing the Inventory Information System (SIPB) in optimizing inventory management, focusing on efforts to improve the company's business sustainability. The specific research objectives include analyzing operational efficiency, evaluating the impact on customer service, assessing business sustainability, identifying challenges and obstacles, and providing a conceptual framework for sustainability. Lalumiere Aesthetics Clinic is a clinic that operates in the field of beauty. One of the activities is inputting incoming and outgoing goods. At the clinic, there is often a shortage of medicine stock in the warehouse, which overwhelms the staff, and there is often an unbalanced amount of stock and the number of goods out, causing many losses to the clinic. So a system is needed that can overcome this problem. After reviewing it again, inventory management at the Lalumiere clinic is still done manually. That is, incoming and outgoing goods are written in a notebook. Hence, errors often occur, such as the number of goods needing to be balanced, causing the company to experience losses. The research method used is a literature study to understand the basic concepts of inventory information systems and the use of Laravel as a website application development framework. Prototype Development to design and develop a prototype inventory information system using Laravel as the main framework. The research results show that implementing an inventory information system using Laravel has increased the company's operational efficiency. Recording, monitoring, and managing inventory becomes more structured and automated, reducing the time required for routine tasks.